Determinants of virological failure among patients on first line highly active antiretroviral therapy (HAART) in Southwest Ethiopia: A case-control study - Bogale, Biruk; Asefa, Adane; Destaw, Alemnew; Midaksa, Gachana; Asaye, Zufan; Alemu Gebremichael, Mathewos; Wolde, Asrat Arja; Yimer, Ejig; Yosef, Tewodros (Frontiers in Public Health, 2022)
Background: Virological failure remains a public health concern among Human Immune Virus (HIV) patients after treatment initiation. Ethiopia is one of the countries that aims to achieve the global target of 90-90-90 that aims to achieve 90% virological suppression, but there is a paucity of evidence on the determinants of virological failure. Therefore, the study intended to assess determinants of virological treatment failure among patients on first-line Highly Active Antiretroviral Therapy at Mizan Tepi University Teaching Hospital (MTUTH), Southwest Ethiopia Method: Hospital-based unmatched case-control study was conducted from 11 November to 23 December 2020, among 146 cases and 146 controls. All cases and controls were selected randomly using computer-generated random numbers based on their medical record numbers. Data were collected through document review using checklists, entered into Epi-data version 4.0.2, and analyzed by SPSS version 25. Multivariable logistic regression analysis was done to identify the independent determinants of virological treatment failure Results: In this study, being male (AOR=1.89, 95%CI: 1.04, 3.47), substance use (AOR = 2.67, 95% CI: 1.40, 4.95), baseline Hgb <12 mg/dl (AOR=3.22, 95%CI: 1.82, 5.99), poor drug adherence AOR 3.84 (95%CI: 1.77, 5.95) and restart ART medication AOR 2.45 (95% CI: 1.69, 7.35)and OI while on HAART (AOR=4.73, 95%CI: 1.76, 12.11) were a determinants of virological treatment failure. Conclusion: The study revealed that the sex of the patient, history of substance use, baseline Hgb < 12mg/dl, poor drug adherence, restart after the interruption, and having OI through the follow-up period were determinants of virological failure. Therefore, program implementation should consider gender disparity while men are more prone to virological failure. It is also imperative to implement targeted interventions to improve drug adherence and interruption problems in follow-up care. Moreover, patients with opportunistic infection and restart HAART need special care and attention.